Design of Trolox Compounds as Antioxidant and Their Analysis Using Quantitative Structure Activity Relationship - Hasmalina Nasution; Nur Enizan; Nurlaili Nurlaili; Jufrizal Syahri (Acta Chimica Asiana, 2020)
Antioxidant compound can inhibit the oxidation of lipids and other biomolecules. The role of antioxidants is very important in neutralizing and destroying free radicals that can cause the damage to cells in the body. This research was carried out to design trolox derivate compounds as antioxidants using the QSAR method. The semi empirical AM1(Austin Model 1)method was used to generate the QSAR model. The statistical analysis result using multiple linier regression methods revealed thet antioxidant activity was influenced by the descriptors of qC1, qC4, qO7, qC13 and qO18. The QSAR equation model obtained was log IC50 = 0.821 + 7.067 (qC1) + 2.585 (qC4) + 4.812 (qO7) – 5.363 (qC13) – 0.887 (qO18) with the best predicted IC50 value was 4.699 µM. Keywords: Antioxidants, QSAR, semi empirical AM1, trolox